Ostian context of the "Roman elegy" of Alexandra Petrova - Fokina, Svetlana (Slavia Centralis, 2022)
The discursive contexts of the lyrical plot of A. Petrova beat the socio-psychological, historical, mythological aspects of the Roman semiosphere, including Ostia Antika and Lido di Ostia. The creation of A. Petrova’s "Roman elegy" potentially as a special subspecies of the elegiac genre that preserves the memory of its great predecessors, allows us to rethink the role behaviour corresponding to the ancient Roman prototype. A. Petrova, for her lyrical plot, chooses a somewhat unconventional Roman locus, which is Ostia. In the modern "Roman elegy" it is promising to consider the author’s transformation of mythological models related to love themes and separation.